Humoral immunity to influenza and severe influenza cases in Russia in 2018-2019 - T. N. Ilyicheva; A. G. Durymanov; E. V. Ivanova; V. A. Zhirnov; A. V. Epanchintseva; S. V. Svyatchenko; P. Yu. Torzhkova; Yu. A. Bulanovich; A. B. Ryzhikov (Медицинская иммунология, 2020)
The aim of our work was to investigate the herd immunity to influenza viruses among population of Russia during autumn 2918; evaluation of severe cases of the infection over the season of2018-2019 epidemics, and confirmed cases of influenza in vaccinated persons. A total of 1835 samples of blood serum were studied. Neither sample did react in hemagglutination inhibition test with highly pathogenic A(H5N8) and A(H7N9) viral strains. 41 to 58% of samples, dependent on sampling region, showed significant antibody titers (> 40) against против вакцинного штамма the vaccinal A/Michigan/45/2015 strain (H1N1pdm09). 40 to 63% of the same sera were positive for epidemic A/Lipetsk/1V/2018 strain (H1N1pdm09), isolated at the start of epidemic season (26.11.2018). From 26 to 46% of the samples were seropositive towards vaccinal strain A/Singapore/ INFIMH-16-0019/2016 (H3N2), and 10 to 23% towards Yamagata influenza B genetic strain. Severe influenza cases during the 2018-2019 epidemic season were caused, mainly, by influenza A virus, with predominance of A/H1N1pdm09 (52.5%), with only 3% of cases caused by influenza A viruses. 217 cases of influenza with lethal outcome were confirmed, of them about a half of these cases (44.7%) affected older persons (> 60 years old), 29% were diagnosed in the group of 46-59 years old. Eight lethal cases of influenza infection (3.7%) were documented in the persons vaccinated before the vaccination season. Over 75% of patients with lethal influenza cases had concomitant diseases, with cardiovascular disorders, obesity, diabetes, urogenital diseases, infectious diseases (HIV, hepatitis) being most often. Hence, vaccination against influenza remains the most effective protective tool, especially in the risk groups. The study was performed in the frames of the state task contract (ГЗ-1/16 and ГЗ-2/18).